Proof: Square Root of a Square
Let's prove the following theorem:
If we square a number and then take the square root of the result, then the output is the original number. Here are some examples:
(3 ⋅ 3)^(1 / 2) = 9^(1/2) = 3
(125 ⋅ 125)^(1 / 2) = 125
(x + 3 ⋅ x + 3)^(1 / 2) = x + 3
High-Level Proof
(x⋅x) = x2, so
x⋅x^1/2 = x21/2
We claim that
x21/2 = x(2 ⋅ 1/2)
2 ⋅ 1/2 is 1, so x(2 ⋅ 1/2) == x
Please log in to add commentsProof:
#
Claim
Reason
1
x ⋅ x = x2
x ⋅ x = x2
2
(x ⋅ x)(1 / 2) = (x2)(1 / 2)
if x ⋅ x = x2, then (x ⋅ x)(1 / 2) = (x2)(1 / 2)
3
(x2)(1 / 2) = x(2 ⋅ (1 / 2))
(x2)(1 / 2) = x(2 ⋅ (1 / 2))
4
2 ⋅ (1 / 2) = 1
2 ⋅ (1 / 2) = 1
5
x(2 ⋅ (1 / 2)) = x1
if 2 ⋅ (1 / 2) = 1, then x(2 ⋅ (1 / 2)) = x1
6
x1 = x
x1 = x
7
(x ⋅ x)(1 / 2) = x
if (x ⋅ x)(1 / 2) = (x2)(1 / 2) and (x2)(1 / 2) = x(2 ⋅ (1 / 2)) and x(2 ⋅ (1 / 2)) = x1 and x1 = x, then (x ⋅ x)(1 / 2) = x
Comments